Investigating the Moderating Role of Moderation Cash in the Relationship between Unconditional Conservatism and Bankruptcy Risk - Esmaeil Eghdami; Sadegh Yousef Nezhad; Maedeh Pendashteh (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: The present study investigates the relationship between unconditional conservatism and bankruptcy risk and the moderating role of cash in this relationship.Methodology: The method used in the present study is a descriptive correlation. With this end in view, in the present study, Beaver and Ryan's (2000) model was used to measure unconditional conservatism, and Altman's (1968) model, which provides a range of bankruptcy probabilities, was used to measure bankruptcy risk. This study also attempts to investigate the moderating role of cash on the relationship between unconditional retention and bankruptcy risk. For this purpose, samples of 140 companies were systematically selected over ten years from 1389-1389 and analyzed using the logistic model for panel data.Findings: The study's results showed that unconditional conservatism increases the risk of corporate bankruptcy. However, no evidence was found concerning the relationship between the interactive variable of unconditional conservatism and cash that might lead to corporate bankruptcy risk.Originality/Value: According to the present research, conservatism can help reduce the risk of bankruptcy. Therefore, in addition to benefiting shareholders from this issue at the macroeconomic level, it can also be helpful.